2022
DOI: 10.1002/agt2.278
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of clusteroluminescence in carbonyl‐based aliphatic polymers

Abstract: Clusteroluminogens (CLgens), nonconjugated structures with visible luminescence at the clustering state, have recently received remarkable attention due to their great theoretical significance and practical values. In carbonyl‐based aliphatic polymers, (n, π*) transition of carbonyl groups and the through‐space interactions have been demonstrated to play an important role in their clusteroluminescence (CL) properties, but it is still a big challenge to manipulate their CL at the molecular level. In this work, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 30 publications
1
44
0
Order By: Relevance
“…Recently, there has been a new class of propeller-shaped luminescent molecules with aggregation-induced emission (AIE) behaviors, which usually have a large Stokes shift due to the significant excited-state conformational change. Besides, compared with the conventional planar π-conjugated luminophores, the emission of twisted AIE luminophores could be attributed to the effective through-space interaction (TSI) among different subunits . Scientists have discovered some special nonconjugated AIE luminophores which have more flexible conformation and stronger TSI than conjugated systems. Thus, this intrinsic feature of nonconjugated luminophores may offer the possibility of manipulating the excited-state processes by the odd–even effect.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a new class of propeller-shaped luminescent molecules with aggregation-induced emission (AIE) behaviors, which usually have a large Stokes shift due to the significant excited-state conformational change. Besides, compared with the conventional planar π-conjugated luminophores, the emission of twisted AIE luminophores could be attributed to the effective through-space interaction (TSI) among different subunits . Scientists have discovered some special nonconjugated AIE luminophores which have more flexible conformation and stronger TSI than conjugated systems. Thus, this intrinsic feature of nonconjugated luminophores may offer the possibility of manipulating the excited-state processes by the odd–even effect.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure , there are two peaks with a stacking distance of 8.72 and 5.10 Å of PMV. Referring to the results of previous theoretical calculations, 5.10 Å is the stacking distance of adjacent MAh. After heating at 170 °C, the stacking peak of MAh becomes more pronounced, while the peak at 8.72 Å weakens. Therefore, we believe that the peak at 8.72 Å is related to randomly entangled polymer chains in particles.…”
Section: Resultsmentioning
confidence: 66%
“…Hence, the factors mentioned above can be considered as nonconventional cluster-triggered emission properties of the polymers originating from multiple intra-and intermolecular interactions like arising from n−π* or π−π* transitions between electron-rich −C�C−, −N�N−, −N−N−, and the conjugated aromatic tetrazole units. 59,67 Thus, we inferred that polymers possessed cluster-induced emission (CTE) characteristic. Subsequently, light-initiated (λ = 365 nm) thiol-ene photo-click reaction approach was performed for the post-polymerization reaction of alkene-functionalized P3 and P7.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…In a previous study, we have demonstrated the synthesis of (bis) 1,5-di-substituted tetrazole-containing monomers via Ugi-azide-four-multicomponent reaction (UA-4MCR) and their respective polymerization via thiol-ene chemistry . It has been observed that the pendant group 1,5-DS-T containing polymers showed interesting luminescence properties since electron-rich heteroatoms (i.e., N, O, and P), hydroxyl (OH), amino (NH2), carbonyl (CO), cyano (CN), amide (CONH), anhydride, and carbon–carbon double bonds (CC) can form diverse clusters upon aggregation that is termed as the clustering-triggered emission (CTE) . Inspired by the mentioned research, we have investigated the respective photophysical properties of main chain 1,5-DS-T-based polymers P1–P7 via ultraviolet–visible (UV–vis) and fluorescence spectroscopy.…”
Section: Results and Discussionmentioning
confidence: 99%